Calyx to Parenchymal Ratio (CPR): An unexplored tool and its utility in the follow-up of pyeloplasty. Issue 2 (April 2021) - Gharpure, Ketaki V.; Jindal, Bibekanand; Naredi, Bikash Kumar; Krishnamurthy, Sriram; Dhanapathi, H.; Adithan, Subathra; Kumaravel, S.; Govindarajan, K.K.
Summary: Introduction: Antero-posterior trans pelvic diameter (APD) and renal scintigraphy play a significant role in the diagnosis of pelvi–ureteric junction (PUJ) obstruction and postoperative follow-up following pyeloplasty. However, the APD varies irrespective of improvement, deterioration, or preserved function in a hydronephrotic kidney and is not a reliable parameter due to various factors (hydration status, compliance, and reduction pyeloplasty). Calyx to Parenchymal Ratio (CPR) is the ratio of the depth of the calyx and parenchymal thickness measured on ultrasound (USG) in coronal image. We assessed the utility of CPR in the follow up of pyeloplasty and compared it with the commonly used APD of the pelvis and renal scintigraphy. Material and methods: A prospective cohort study was done from July 2016 to October 2017. During this period 73 pyeloplasties were done, and 62 cases meeting the inclusion criteria were enrolled. All the children underwent ultrasound and Technetium-99 m Ethylene dicysteine isotope renogram (EC) scan before and after pyeloplasty. APD and CPR values were measured on USG and compared with isotope renogram outcomes in these children in the preoperative versus postoperative period. Two defined objective variables ΔAPD, percent ΔAPD and ΔCPR, percent ΔCPR were compared with categorical variables that would predict the surgical outcome as - failed, successful or equivocal. Multinomial logistic regression analysis and receiver operating curve (ROC) analysis was used to identify predictive accuracy. Results: The mean (range) APD value recorded in the preoperative period was 3.67 cm (1.40–8.00 cm), which decreased to 1.67 cm (0.40–6.50) postoperatively, which was 54.2% lower (P=<0.001). The mean (range) CPR value decreased from 5.96 (1.20–20.00) in the preoperative period to 2.57 (0.43–10.90) postoperatively, which was 56.8% lower (P=<0.001). On multinomial logistic regression analysis, ΔCPR was found to be a significant predictor of outcome with an overall accuracy of 95.1%, change in CPR was a better predictor of success after pyeloplasty as compared to change in APD, which had an overall accuracy of 85.2% (p = 0.01). Further, on ROC curve analysis, we observed that ΔCPR and %ΔCPR can strongly predict successful pyeloplasty with a sensitivity of each with 96% and 98% respectively and AUC of 0.897 and 0.799 respectively. Discussion: USG (APD) and renogram are the most widely used investigation in follow-up of pyeloplasty; however, APD has its own limitations like operator variability and slower improvement. CPR has the advantages that neither calyceal depth nor parenchymal thickness is directly altered during the surgery, and early resolution of calyceal dilatation and rapid parenchymal growth following pyeloplasty and thus a surgeon independent parameter. Our results have shown that ΔCPR can identify successful pyeloplasty with strong prediction than ΔAPD and thus renal scans can be avoided if there is visible improvement in CPR on follow-up. Conclusions: Our study identified a change in CPR, i.e., ΔCPR as a strong predictor of surgical outcome, as it is not influenced by extent of pelvis reduction during pyeloplasty and early to change. Using this parameter, we can avoid unnecessary repeated nuclear scans based on persistent high APD values and optimize resource utilization. We recommend the use of CPR in routine practice in the preoperative and postoperative follow-up of PUJ obstruction following pyeloplasty. Summary Table ROC curve analysis of ΔCPR and ΔAPD and percent ΔCPR and percent ΔAPD in predicting surgical outcome following pyeloplasty Summary Table Parameters Cut-off value Sensitivity Specificity AUC 95% Confidence Interval (CI) p- value Δ CPR 0.4 96.08% 75% 0.897 0.785 to 0.963 0.0001 Δ APD 1.3 68.63% 75% 0.615 0.474 to 0.743 0.503 %Δ CPR 12.5 98.04% 75% 0.799 0.669 to 0.895 0.137 % ΔAPD 41.25 80.39% 75% 0.848 0.726 to 0.931 0.0001